A circulating anticoagulant occurring after temporal arteritis and controlled by corticosteroid therapy - Whitfield, A. G. W. (1962)
A case is described in which a circulating anticoagulant, inhibiting antihaemophilic globulin, developed following temporal arteritis. The circulating anticoagulant disappeared with steroid therapy, reappearing when steroids were withdrawn. Permanent maintenance therapy appears necessary in this case to prevent haemorrhagic manifestations.